The Study of Factors Influencing the Movement of Inflation in Thailand - Adinan Al-Mustafa (Efficient: Indonesian Journal of Development Economics, 2023)
The main cause of inflation is excessive demand for goods and services that exceeds the capacity to supply them, often due to increased production costs. This leads producers to adjust prices upward or reduce production. In the context of energy-related products, such as fossil fuels, electricity, and cooking gas, they constitute a significant portion of production costs for many goods and services. This study used quantitative research, and data were collected by the documentation method with secondary data from 1998–2022, using autoregressive distributed lag (ARDL) as a method for data analysis. Based on the results of the analysis, it was found that oil prices have a significant positive influence on inflation, both in the short run and the long run. Government expenditures have a significant negative influence on inflation, both in the short run and the long run. The money supply has a significant positive influence on inflation, both in the short run and the long run. Average monthly wages have a significant positive influence on inflation in Thailand, but only in the short run. The unemployment rate has a significant negative influence on inflation, but only in the short run.